Antitrust, Patents, and Cumulative Innovation: Evidence from Bell Labs - Markus Nagler; Martin Watzinger; Thomas Fackler; Monika Schnitzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
How large is the impact of intellectual property on cumulative innovation in electronics, computers and communications? Following an antitrust lawsuit against Western Electric and AT&T, Bell Labs had to license all patents published by 1956 for free. We find that this removal of patent rights increased subsequent citations to Bell's patents by 7%. Patenting in affected patent subclasses increased by 17%. The effect comes from young and small firms in fields in which Bell did not remain commercially active. Placebo regressions support the identification assumption of parallel trends in citations.
Keywords: O31; O33; L43; 330